Impact of Online Social Media Usage Behavior on Perceptions of Thai Polysemous Words among Chinese Students Studying Thai Language in Guangxi Zhuang Autonomous Region, China - Leelapornpinit, Sunee; Sikakaew, Penpisut; Nikornsawat, Prapatsorn; Lan, Xialing (Journal of Man and Society, 2024)
The purpose of this research is to study the online social media usage behavior which affects on the perception of Thai polysemous words among Chinese students studying Thai language in the Greater China region, particularly in Guangzhou area by utilize the mixed method. Data was collected from 108 Chinese students at the undergraduate level, specifically in their third and fourth years. The research tools used for data collection were questionnaires. Statistics used for data analysis included mean and standard deviation, and statistics for hypothesis testing were one-way analysis of variance. The results indicate that the type of online social media that Chinese students mostly use is TikTok, and the predominant platform is Google’s website. In terms of online social media used for learning and developing Thai language skills is dramas, the majority of students spend 1 to less than 2 hours using these platforms. Regarding the frequency of using Thai platforms and Thai online social media per week, it was found that the majority of Chinese students do not use them. Yet, the media’s potential to convey stories about multiple words to Chinese learners is not yet fully available.The research indicates that factors related to ethnicity have no statistically significant impact on the frequency of using Thai platforms and watching online media. On the other hand, factors related to academic year have a statistically significant impact (<0.05) on the frequency of watching online social media. The usage behavior of online social media for learning and developing Thai language skills among Chinese students tends to involve more “consumption” rather than “active use”. Opinions about the behavior of using online social media which affects on the perception of Thai polysemous words are moderately in agreement. The topic that students mostly agree with is that regularly using online social media helps them become more familiar with Thai polysemous words. They also find examples of the use of multiple meanings in different sentences.